Social Entrepreneurship for Inclusive Growth in the Democratic Republic of Congo - Agapitova, Natalia; Apedo Amah, Marie Christine; Tinsley, Elaine (World Bank, Washington, DC, 2021)
While its poverty rate has fallen slightly over the past two decades, the DRC remains one of the poorest countries in the world. The unaddressed demand for service delivery will require local private sector solutions to meet the needs of the poor, marginalized, and other underserved populations. Social enterprises (SEs) champion emerging private sector solutions to bring services to these populations, by switching from charity-based, donor-dependent organizations to revenue generating and sustainable enterprises. This report provides an overview of opportunities for, and constraints to, social entrepreneurship in the DRC and lays out a menu of options for strengthening social entrepreneurship through development programs.